Numerical study of a tangentially fired boiler for reducing steam tube overheating. (5th June 2016) - Tang, Guangwu; Wu, Bin; Johnson, Kurt; Kirk, Albert; Fu, Dong; Zhou, Chenn Q.
Highlights: CFD study on a tangentially fired boiler firing metallurgical gases was conducted. Experimental flame profile and numerical simulation results shows great agreement. The hot spots were identified based on a wide range of typical operating conditions. Low load fuel input would lead to flame impingement onto the steam tubes. Around 2 percent (volume) natural gas input is the optimal value for operation. Abstract: A comprehensive numerical and experimental study on a 200 MW tangentially fired boiler firing metallurgical gases was conducted. A three-dimensional Computational Fluid Dynamics (CFD) model was developed to simulate the flow characteristics and combustion process inside the boiler. The eddy dissipation concept combustion model was applied to take into account detailed turbulent interactive reacting chemical reactions. Field experiments were also conducted on the original tangentially fired boiler under different operation conditions. Flame profiles videos were captured during experiments. A quick comparison of the experimental flame profile with numerical simulation results shows good agreement. Wall steam tubes overheating problem was observed, and the hot spots were identified based on a wide range of typical operation conditions. The effect of total fuel input and natural gas percentage on the furnace wall temperature were investigated.